PENGARUH MOTIVASI, KEMAMPUAN DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA PERAWAT PELAKSANA DI RUMAH SAKIT ISLAM (RSI) AISYIYAH MALANG - Riezky Amalia (Adbis: Jurnal Administrasi dan Bisnis, 2017)
The aims of this research is to analyze an effect of motivation, ability dan organizational commitment to operational nurse’s performance at Malang Aisyiyah Islamic Hospital. The object of this study is the 67 operational nurse’s at Malang Aisyiyah Islamic Hospital. All of the nurses became the respondents. Research data were analyzed with the technique of multiple linear regression by using SPSS 11,5 software. The research resulted that the multiple coefficient regression showed that there was simultaneously significant influence among independent variables to dependent variable. This meant that variables of motivation, ability and organizational commitment significantly influenced the nurse’s performance.